Modernizing education in the post-secular world - Syusyukin, Vladimir Alekseevich (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2022)
Introduciton. This article examines the main directions of modernization of the institution of education in a post-secular society; socio-philosophical analysis of the transformations of modern education is carried out at various levels of its institutionalization: educational and methodological, organizational and managerial, communicative, value-semantic, etc. Theoretical analysis. In addition, the author of the work explores the cognitive features of the perception of modern education as an institution that includes elements of both secular and religious cultures. Conclusions. At the end of the work, the author comes to the following conclusions: the modern institution of education must be transformed under the infl uence of the most complex processes of modernity. In the conditions of the post-secular world, not only the very perception of education as a social institution is changing, but also its paradigmatic foundations, which in turn determines the formation of a qualitatively new policy in the fi eld of higher education personnel. Using the example of theologians and religious scholars, it is shown that in the conditions of post-secularity, these specialists are no longer only theoretical researchers, but also valuable experts in the humanities who are able to qualitatively analyze contradictory ethno-confessional and social relations at the regional and federal levels, as well as off er practical solutions to the most important strategic objectives of the state.